(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the constipation problems of nursing students and the variables that affect it.Material and Methods: The research was conducted on the first, second, third and fourth year students of Batman University School of Nursing in 2018-2019 academic year. The sample of the study consisted of 218 nursing students who accepted to participate voluntarily. In the collection of data, a “Student Information Form” and the “Constipation Severity Scale” (CSS) were used. Results: The average age of the students included in the study was 21.14±2.34 (17-39 years), 55.5% of the students were female, 33% were in their senior year, 55% were living at home with their parents, 85.6% did not smoke, 93.6% had no chronic disease and 76.6% performed regular exercise. It was found that 56.9% of the students ate three times a day and 38.5% twice a day; 67.9% of the students consumed pulpy or fibrous foods occasionally; the daily average of water consumed by the students was 7.69±4.16 cups and 3.83±2.44 cups of coffee were consumed. The mean total CSS score of the students was 27.83±7.85 and the mean scores of the sub-scales were calculated as “Intestinal Obstruction”12.53±3.48, “Lazy Bowels” 11.56±3.84 and “Pain” 2.29±2.62. It was determined that there were differences between the variables of gender, exercise status, consumption of pulpy or fibrous foods and the daily consumption of tea or coffee and the mean score of CSS.Conclusion: It was observed that there were the incidence of constipation was not very high in nursing students and that this problem was experienced more by students who did not perform exercise, who consumed less pulpy or fibrous food, and who were female.Keywords: Constipation; health status; nursing students.